2017
DOI: 10.1097/cad.0000000000000539
|View full text |Cite
|
Sign up to set email alerts
|

Solid lipid nanoparticles improve octyl gallate antimetastatic activity and ameliorate its renal and hepatic toxic effects

Abstract: Metastasis is the main cause of cancer-related death and requires the development of effective treatments with reduced toxicity and effective anticancer activity. Gallic acid derivatives have shown significant biological properties including antitumoral activity as shown in a previous study with octyl gallate (G8) in vitro. Thus, the aim of this work was to evaluate the antimetastatic effect of free and solid lipid nanoparticle-loaded G8 in mice in a lung metastasis model. Animals inoculated with melanoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Studies with other food additives (Collison et al, 2013[ 4 ]; Chen et al, 2017[ 3 ]; Jensen et al, 2018[ 16 ]) or therapeutic drugs (Gentilucci et al, 2006[ 14 ]; Menter et al, 2009[ 23 ]; Zhao et al, 2014[ 36 ]) have also found lipid accumulation in the liver. Our results are also in agreement with an in vivo study showing that OG induced liver toxicity, as its treatment increased the oxidative stress (Cordova et al, 2017[ 5 ]). Considering that the excess of free fatty acids increases the production of reactive oxygen species (Svegliati-Baroni et al, 2019[ 30 ]), it is possible that these mechanisms are associated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Studies with other food additives (Collison et al, 2013[ 4 ]; Chen et al, 2017[ 3 ]; Jensen et al, 2018[ 16 ]) or therapeutic drugs (Gentilucci et al, 2006[ 14 ]; Menter et al, 2009[ 23 ]; Zhao et al, 2014[ 36 ]) have also found lipid accumulation in the liver. Our results are also in agreement with an in vivo study showing that OG induced liver toxicity, as its treatment increased the oxidative stress (Cordova et al, 2017[ 5 ]). Considering that the excess of free fatty acids increases the production of reactive oxygen species (Svegliati-Baroni et al, 2019[ 30 ]), it is possible that these mechanisms are associated.…”
Section: Discussionsupporting
confidence: 93%
“…An animal model study showed that OG, at high doses, was able to induce strong inhibition of gluconeogenesis, which could be considered as harmful (Eler et al, 2015[ 10 ]). In addition, OG has been shown to induce toxicity in mice liver, as its use increased serum levels of AST and ALT, oxidative stress and histological damage (Cordova et al, 2017[ 5 ]). However, no studies have evaluated its effect on lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, SLPs have been demonstrated to be effective against metastasis using chemotherapeutic drugs such as paclitaxel [58], etoposide [59], and gallic acid ester derivatives [60], among others. Our results indicate that these particles exhibit a higher antimetastatic effect than unformulated DOX without any detectable toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the notable investigations on SLNs that endowed extraordinary results against skin cancer include omega-3 α-linolenicacid/ α-tocopheryl linolenate, sodium taurocholate, tween 20/ melanoma [ 308 ] , Mentha longifolia , Mentha pulegium essential oils/ stearic acid, span 60, tween 80/ melanoma [ 309 ] , octyl gallate/ Astrocaryum murumuru (seed butter), tween 80/ melanoma [ 310 ] , doxorubicin/ lecithin, sodium taurodeoxycholate/ melanoma, squamous cell carcinoma [ 311 ] , paclitaxel/ stearic acid, egg lecithin/ squamous cell carcinoma [ 312 ] , microRNA-34a, paclitaxel/ glyceryl monostearate, cholesterol, soy phosphatidylcholine, dimethyldioctadecyl ammonium bromide/ melanoma [ 313 ] .…”
Section: Lipid-based Nanoparticles For Skin Cancer Therapymentioning
confidence: 99%